2019
DOI: 10.14499/indonesianjcanchemoprev10iss3pp131-139
|View full text |Cite
|
Sign up to set email alerts
|

Compound Identification and Anticancer Activity of Ethyl Acetate Fraction from Bawang Sabrang (Eleutherine palmifolia (L.) Merr.) on HeLa Cervical Cancer Cell Line

Abstract: Eleutherine palmifolia (L.) Merr. is a typical plant found in Central Kalimantan that has been used empirically by the Dayak people as medicine for various diseases, including cancer. The plant contains flavonoid compounds that potentially used as an anticancer. The purpose of this study is to find the most active fraction, indicated by its cytotoxic potency on HeLa cervical cancer cell line, and to identify compounds in E. palmifolia bulbs fraction. E. palmifolia bulbs was extracted by maceration. The extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
0
9
0
4
Order By: Relevance
“…Natural ingredients proven to have anticancer properties include resveratrol. [ 12 13 ] Our findings showed that resveratrol had good bioavailability and interacted with genes associated with lung cancer. Consistently, resveratrol might be involved in the biological process of lung cancer either the P53 signaling pathway (Hsa04115), MicroRNAs in cancer (Hsa05206), and Apoptosis (Hsa04210) either in small-cell lung cancer (Hsa05222) or nonsmall-cell lung cancer (Hsa05223) from network pharmacology followed by PPI network analysis.…”
Section: Discussionmentioning
confidence: 84%
“…Natural ingredients proven to have anticancer properties include resveratrol. [ 12 13 ] Our findings showed that resveratrol had good bioavailability and interacted with genes associated with lung cancer. Consistently, resveratrol might be involved in the biological process of lung cancer either the P53 signaling pathway (Hsa04115), MicroRNAs in cancer (Hsa05206), and Apoptosis (Hsa04210) either in small-cell lung cancer (Hsa05222) or nonsmall-cell lung cancer (Hsa05223) from network pharmacology followed by PPI network analysis.…”
Section: Discussionmentioning
confidence: 84%
“…Fluorescence intensity was measured using the FL-1H parameter to detect FITC. Subsequently, the percentage of apoptosis was analyzed using the Cell Quest software (BD Bioscience) [19].…”
Section: Apoptosis Assaymentioning
confidence: 99%
“…In addition, the research also found the compound content, namely the group of naphthoquinone (C35H36O14) with a high percentage of area. Not only that, the analysis of the content of naphthoquinone and its derivatives has also been proven using UHPLC [2,3]. The SNEDDS formula used was the optimal formulation in the form of 50 mg / 10 ml Dayak onion extract, 10% caprylic triglycerides as oil, 1% tween 80 and 6.61% transcutol as a combination surfactant, and 12.389% propylene glycol as a co-surfactant, while the formula Dayak extract solution as a comparison used was 50 mg / 10 ml methanol p.a.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…There are many compounds possessed by Dayak onions. It also has antioxidant activity, which isoliquiritigenin (C15H11O4) included to flavonoid (chalcone) and oxyresveratrol (C14H12O4) included to polyphenol (stilbene) [2]. Other research related to the content of compounds in Dayak onion extract also states that there is a content of naphthoquinone in Dayak onion plants [3].…”
Section: Introductionmentioning
confidence: 99%